IMPLIKASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA SISWA MADRASAH IBTIDAIYAH - Kamal (CBJIS : Cross-Border Journal of Islamic Studies, 2021)
This study aims to analyze the issue of character education as a hot topic of discussion in the world of education, including the world of Islamic education in Indonesia. The formation of student character in Islamic educational institutions such as madrasas is a good thing to do. The research method uses a descriptive qualitative approach with a literature review. The results of this study indicate that madrasas play a role in producing smart students in science and character and personality. Through the example of Islamic figures and scholars discussed in Islamic Cultural History learning, especially the patience, persistence, and fortitude of the Prophet Muhammad SAW, his companions, scholars, and major figures in Islam so that several characters are built for students such as religious, honest, disciplined, responsible, independent, social care and hard work